2004
DOI: 10.1016/j.biolcel.2004.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Glial fibrillary acidic protein (GFAP)‐like immunoreactivity in the visual system of the crab Ucides cordatus (Crustacea, Decapoda)

Abstract: Glial fibrillary acidic protein (GFAP) is the main intermediate filament protein used as a marker for the identification of astrocytes in the central nervous system of vertebrates. Analogous filaments have been observed in the glial cells of many mollusks and annelids but not in crustaceans. The present study was carried out to identify by light microscopy immunohistochemistry, immunoelectronmicroscopy and immunoblotting, GFAP-like positive structures in the visual system of the crab Ucides cordatus as additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Again this experiment was confirmed by Western blotting [Fig. (B)], which showed a band at ∼45 kDa, therefore, near the molecular weight of the band described for another invertebrate species, the crab Ucides cordatus (∼48 kDa; Silva et al ) and close to the molecular weight found in mammals (∼48 to ∼50 kDa; Yen and Fields, ; Eng, ).…”
Section: Resultssupporting
confidence: 67%
“…Again this experiment was confirmed by Western blotting [Fig. (B)], which showed a band at ∼45 kDa, therefore, near the molecular weight of the band described for another invertebrate species, the crab Ucides cordatus (∼48 kDa; Silva et al ) and close to the molecular weight found in mammals (∼48 to ∼50 kDa; Yen and Fields, ; Eng, ).…”
Section: Resultssupporting
confidence: 67%
“…The monoclonal antibody used was against glial fibrillary acidic protein (GFAP,-antirabbit IgG; Sigma), diluted at 1:100, which labels glial cells (da Silva et al 2004). The secondary antibody was Alexa 546 (goat anti-rabbit) diluted at 1:600.…”
Section: Histochemistry and Immunohistochemistrymentioning
confidence: 99%
“…The nitrocellulose membrane containing the immobilized proteins was first blocked with non-fat dry milk (5%) plus BSA (1%) in 0.1 M TRIS-buffered saline containing 0.001% Tween (TBS t ), for 90 min. This procedure had previously been used successfully in blotting proteins obtained from the eyestalks of crabs of the same species da Silva et al 2004). After blockage, the membrane was washed twice in TBS t under constant stirring for 3 min.…”
Section: Protein Determination Assaymentioning
confidence: 99%